Dysregulation of Adipose Glutathione Peroxidase 3 in Obesity Contributes to Local and Systemic Oxidative Stress - Lee, Yun Sok; Kim, A Young; Choi, Jin Woo; Kim, Min; Yasue, Shintaro; Son, Hee Jung; Masuzaki, Hiroaki; Park, Kyong Soo; Kim, Jae Bum (Molecular endocrinology (Baltimore, Md.), 2008)
Abstract Glutathione peroxidase 3 (GPx3) accounts for the major antioxidant activity in the plasma. Here, we demonstrate that down-regulation of GPx3 in the plasma of obese subjects is associated with adipose GPx3 dysregulation, resulting from the increase of inflammatory signals and oxidative stress. Although GPx3 was abundantly expressed in kidney, lung, and adipose tissue, we observed that GPx3 expression was reduced selectively in the adipose tissue of several obese animal models as decreasing plasma GPx3 level. Adipose GPx3 expression was greatly suppressed by prooxidative conditions such as high levels of TNFα and hypoxia. In contrast, the antioxidant N-acetyl cysteine and the antidiabetic drug rosiglitazone increased adipose GPx3 expression in obese and diabetic db/db mice. Moreover, GPx3 overexpression in adipocytes improved high glucose-induced insulin resistance and attenuated inflammatory gene expression whereas GPx3 neutralization in adipocytes promoted expression of proinflammatory genes. Taken together, these data suggest that suppression of GPx3 expression in the adipose tissue of obese subjects might constitute a vicious cycle to expand local reactive oxygen species accumulation in adipose tissue potentially into systemic oxidative stress and obesity-related metabolic complications.